Determining a New Warehouse Location for an Electrical Home Appliances Company - KIZILKAYA, İLAYDA; KEVSER, TOLGAHAN; OFLUOĞLU, HANDE; ÖLÇÜCÜER, FEYZA; DEMİREL, DUYGUN FATİH (Springer Science and Business Media Deutschland GmbH, 2024)
In today’s businesses, supply chain management is a critical factor in terms of efficiency, profitability and cost savings. The success of the supply chain is possible with the right management of the rings such as warehousing and logistics activities. Deficiencies in warehouse and logistics management can lead to inefficiencies and errors in the supply chain, which can have negative effects on business profitability and customer satisfaction. Strategic decisions regarding warehouse locations are vital for cost policies. In this study, a warehouse location selection procedure is proposed for an electrical home appliances company considering the distances to the customers, their transaction volumes, and various other costs. The approach is basically a two-stage facility layout problem that first solves a weighted Euclidean minisum model defined on a continuous plane. Then, four alternative locations that are close to the result obtained in the first step are determined. In addition, two lands owned by the firm are added to the set of alternatives. Next, a p-median (1-median) model is solved and the most suitable warehouse location is determined. Through sensitivity analysis, the changes in the solution are searched for various rent values. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
International Symposium for Production Research, ISPR 2023
Keywords: Facility Location Problem; Logistics; p-median; Warehouse Management